Percutaneous coronary intervention: recommendations for good practice and training. (19th December 2005) - Dawkins, K D; Gershlick, T; de Belder, M; Chauhan, A; Venn, G; Schofield, P; Smith, D; Watkins, J; Gray, H H
Abstract : EXECUTIVE SUMMARY: Cardiologists undertaking percutaneous coronary intervention (PCI) are excited by the combination of patient and physician satisfaction and technological advance occurring on the background of the necessary manual dexterity. Progress and applicability of percutaneous techniques since their inception in 1977 have been remarkable; a sound evidence base coupled with the enthusiasm and ingenuity of the medical device industry has resulted in a sea change in the treatment of coronary heart disease (CHD), which continues to evolve at breakneck speed. This is the third set of guidelines produced by the British Cardiovascular Intervention Society and the British Cardiac Society.1, 2 Following the last set of guidelines published in 2000, we have seen PCI activity in the UK increase from 33 652 to 62 780 (87% in four years) such that the PCI to coronary artery bypass grafting ratio has increased to 2.5:1. The impact of drug eluting stents has been profound, and the Department of Health is investigating the feasibility of primary PCI for acute myocardial infarction. Nevertheless, the changes in the structure of National Health Service funding are likely to focus our attention on cost effective treatments and will require physician engagement and sensitive handling if we are to continue the rapid and appropriate growth in our chosen field.3 It is important with this burgeoning development now occurring on a broad front (in both regional centres and district general hospitals) that we maintain our vigilance on audit and outcome measures so that standards are maintained for both operators and institutions alike. This set of guidelines includes new sections on training, informed consent, and a core evidence base, which we hope you will find useful and informative. Keith D Dawkins: President, British Cardiovascular Intervention Society (2000–2004) Huon H Gray: President, British Cardiac Society (2003–2005)